Regulation of Biological Functions at the Cell Interface by DNA Nanostructures. Issue 2 (4th December 2021) - Chen, Yongjian; Tian, Run; Shang, Yingxu; Jiang, Qiao; Ding, Baoquan
Abstract : The control over specific biological functions of a single cell or between different cells is an exciting goal in the fields of biophysics and biochemistry. Besides the fast‐developed chemical biology methods, such as chemical labeling and gene editing, researchers are still seeking for efficient ways to manipulate cell behaviors. Over the past decades, self‐assembled DNA nanostructures have emerged as novel and versatile tools for the study of biological science. Featured with structural programmability, customized functionality, and marked biocompatibility, DNA nanostructures have been immensely exploited for a variety of fascinating biological applications including bioimaging and drug delivery. In addition, DNA nanostructures also hold great potential in the regulation of physiological functions at various biological interfaces. In this minireview, the recent progress of the regulation of biological processes and functions at cell interface using DNA nanostructures is summarized. Current challenges and opportunities in applying DNA nanoassemblies as tools for cell behavior manipulation are also briefly discussed. Abstract : DNA nanostructures have emerged as versatile platforms for the study of various biological processes. Featured with outstanding self‐assembly and multiple functionalization properties, DNA nanostructures have also been exploited for the regulation of physiological functions at cell interface. This minireview summarizes the recent progress in the regulation of biological processes and the subsequent therapeutic effects at cell interface through DNA nanostructures.